Brand management and positioning: a case study in the medical-hospital-dental sector - Akiyama, Fernando Lara; Lima, Gustavo Barbieri; Garcia, Sheila Farias Alves [UNESP]; Galli, Lesley Carina do Lago Attadia [UNESP] (Univ Metodista Piracicaba-unimep, 2022)
The present research aims at investigating how the company ALPHA (medical-hospital-dental sector) strategically manages and positions its brands in the national market, aiming to create a positive and favorable image of the company, as well as to obtain a competitive advantage in the market in which it operates. The case study method was used to analyze the company ALPHA, considered the largest diagnostic medicine company in Brazil and Latin America. The main results pointed out that: (a) the great competitive differentials used in the positioning of the ALPHA brand are: to offer the largest clinical staff in genetics in Brazil and to operate with the most modern infrastructure and equipment on the market, expanding production capacity, ensuring high quality standard and accurate reproduction of exams; (b) as communication tools, ALPHA uses: advertising (television, radio, magazine, newspaper, internet, illuminated poster, display, catalogs and leaflets), sales promotion (gifts, stickers, special discounts), among others.
Keywords: Brand Management; Positioning; Medical-Hospital-Dental Sector